Three‐dimensional surface deformation‐based shape analysis of hippocampus and caudate nucleus in children with fetal alcohol spectrum disorders. Issue 2 (5th November 2012) - Joseph, Jesuchristopher; Warton, Christopher; Jacobson, Sandra W.; Jacobson, Joseph L.; Molteno, Chris D.; Eicher, Anton; Marais, Patrick; Phillips, Owen R.; Narr, Katherine L.; Meintjes, Ernesta M.
<x xml:space="preserve">Abstract</x> Surface deformation‐based analysis was used to assess local shape variations in the hippocampi and caudate nuclei of children with fetal alcohol spectrum disorders. High‐resolution structural magnetic resonance imaging images were acquired for 31 children (19 controls and 12 children diagnosed with fetal alcohol syndrome/partial FAS). Hippocampi and caudate nuclei were manually segmented, and surface meshes were reconstructed. An iterative closest point algorithm was used to register the template of one control subject to all other shapes in order to capture the true geometry of the shape with a fixed number of landmark points. A point distribution model was used to quantify the shape variations in terms of a change in co‐ordinate positions. Using the localized Hotelling T2 method, regions of significant shape variations between the control and exposed subjects were identified and mapped onto the mean shapes. Binary masks of hippocampi and caudate nuclei were generated from the segmented volumes of each brain. These were used to compute the volumes and for further statistical analysis. The Mann–Whitney test was performed to predict volume differences between the groups. Although the exposed and control subjects did not differ significantly in their volumes, the shape analysis showed the hippocampus to be more deformed at the head and tail regions in the alcohol‐exposed children. Between‐group differences in caudate nucleus morphology were dispersed across the tail and head regions. Correlation analysis showed associations between the degree of compression and the level of alcohol exposure. These findings demonstrate that shape analysis using three‐dimensional surface measures is sensitive to fetal alcohol exposure and provides additional information than volumetric measures alone. Hum Brain Mapp 35:659–672, 2014. © 2012 Wiley Periodicals, Inc.